Relación entre la balanza comercial y el empleo formal: evidencia para Loreto periodo 2018 – 2022 - D'azevedo Reátegui, Jorge Severino (2024)
This thesis aims to investigate the relationship between the trade balance and formal employment in the Loreto region from 2018 to 2022. A linear regression model, applying classical least squares, was used to test the general hypothesis of a positive relationship between these variables. The results, assessed through statistical tests such as the Student's t-test and the p-value, showed a significant positive link, evidenced by a positive coefficient for the trade balance. In addition, specific hypotheses were examined, including one about the positive correlation, measured by the Pearson correlation coefficient, and another about the level of influence of the trade balance on formal employment, evaluated using the coefficient of determination and its adjusted version. The findings confirmed a moderate positive correlation and a significant, although not dominant, impact of the trade balance on formal employment, thus supporting the general hypothesis and the specific ones proposed in the study.